Driving Sustainable Growth through the Blue Economy: Empirical Evidence from Indonesia’s Transport and Logistics Companies - Atikah, Mutia; Haryanto, Haryanto (Universitas Negeri Padang, 2026)
The increasing awareness of environmental degradation has drawn significant attention to sustainable business practices; however, the blue economy concept remains underexplored despite its crucial role in maintaining oceanic balance and supporting national economic growth. This study aims to analyze the effect of blue economy implementation and corporate social responsibility on the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange during 2022–2024. Using a quantitative panel-data approach with secondary data from annual and sustainability reports, the study measures blue economy implementation through a disclosure index adapted from national sustainability frameworks, while financial performance is proxied by return on assets. The novelty of this research lies in focusing on the transportation and logistics sector, which plays a vital role in maritime-based economic growth but has received limited attention in sustainability accounting studies. The results indicate that blue economy implementation has a positive and significant influence on financial performance, suggesting that environmentally responsible practices enhance corporate accountability and stakeholder trust. Conversely, corporate social responsibility disclosure shows a negative yet significant relationship with financial performance, implying a short-term trade-off between social responsibility efforts and profitability. Firm size and leverage are found to be insignificant, while firm age exhibits a negative tendency toward profitability. These findings underscore the need for companies and regulators to strengthen blue economy practices as a long-term strategy for sustainable financial growth and to develop standardized blue economy disclosure frameworks for future research.